2020
DOI: 10.1101/2020.06.11.146878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Colon Cancer and SARS-CoV-2: Impact of ACE2 Expression in Susceptibility to COVID-19

Abstract: Novel coronavirus disease (COVID-19) pandemic has become a global health emergency. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) interacts with angiotensin-converting enzyme 2 (ACE2) to enter the cells and infects diverse human tissues. It has been reported that a few conditions, including cancer, predispose individuals to SARS-CoV-2 infection and severe form of COVID-19. These findings led us to evaluate the susceptibility of colon adenocarcinoma (COAD) patients to SARS-CoV-2 infection by inve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…More than 80% of people have shown mild to moderate infection, while the remaining portion would progress to severe and critical conditions. Older people and people with comorbidity, especially cardiovascular disease, diabetes, mostly make up the population of those dying from COVID-19 (Ahmadi et al 2020;Hessami et al 2020;Shamshirian and Rezaei 2020;Sahu et al 2020). However, the observation of severe infection and death from infection in young people and people without a preexisting condition has pointed to the possible role of genetics in susceptibility to COVID-19 (Ahanchian et al 2020;Darbeheshti and Rezaei 2020;Yousefzadegan and Rezaei 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More than 80% of people have shown mild to moderate infection, while the remaining portion would progress to severe and critical conditions. Older people and people with comorbidity, especially cardiovascular disease, diabetes, mostly make up the population of those dying from COVID-19 (Ahmadi et al 2020;Hessami et al 2020;Shamshirian and Rezaei 2020;Sahu et al 2020). However, the observation of severe infection and death from infection in young people and people without a preexisting condition has pointed to the possible role of genetics in susceptibility to COVID-19 (Ahanchian et al 2020;Darbeheshti and Rezaei 2020;Yousefzadegan and Rezaei 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Further assessment showed that the ACE2 gene promoter is hypomethylated in COAD patients and the methylation status is negatively correlated with ACE2 expression. On the other hand, ACE2 gene expression positively correlated with infiltration level of immune cells including memory B cell, plasma B cell, activated myeloid dendritic cell, and resting myeloid dendritic cell in COAD patients [59]. SARS-CoV-2 infection was shown to reduce ACE2 level post-infection [58], which would bring poor prognosis for patients with colon cancer due to altered immune cell infiltration level.…”
Section: Role Of Molecular Aberrations and Genetic Changes Associatedmentioning
confidence: 91%
“…Analyzing the expression of ACE2 in various tumor tissues has been also used to evaluate the susceptibility of these patients to SARS-CoV-2 infection. Ahmadi et al [59] showed that ACE2 mRNA and protein levels were higher in colon adenocarcinoma (COAD) patients than in the control group, suggesting more susceptibility to COVID-19. This upregulation was not correlated with patient survival outcomes.…”
Section: Role Of Molecular Aberrations and Genetic Changes Associatedmentioning
confidence: 99%
“…Cancer patients are more susceptible to SARS-CoV-2 and are more likely to develop severe COVID-19. 84,85 It remains unclear if anti-PD-1/PD-L1 treatment would be beneficial for COVID-19 patients. Immune checkpoint inhibitors (ICI) may enhance the cytokine storm associated with higher COVID-19 morbidity and mortality.…”
Section: Time-series Transcriptomics Reveals That Sars-cov-2 Induces ...mentioning
confidence: 99%